Literature Review: Online Marketing Activities Towards Increasing The Income of Traditional Market Traders in South Sulawesi - Supri; Sahabuddin, Romansyah; Amin, Andi Nurzakiah; Sulolipu, Andi Annisa (PT. Maju Malaqbi Makkarana, 2024)
Online marketing is one of the main strategies in increasing business income, including for traditional market traders in South Sulawesi. Although internet penetration in Indonesia, especially in South Sulawesi, continues to grow, many traditional market traders have not utilized digital potential to market their products. This study aims to explore online marketing activities implemented by traditional market traders in Gowa Regency, as well as to analyze their influence on increasing income and the factors that influence their success. Based on literature studies, the use of social media and e-commerce platforms has been shown to increase product visibility and attract more consumers, which in turn can increase sales. However, the adoption of digital technology among traditional market traders is still limited, mainly due to the lack of skills in managing social media accounts and digital platforms. This study uses a qualitative approach with interviews and observation methods of traders in traditional markets in Gowa Regency. The results of the study show that online marketing has a positive influence on increasing trader income, but the level of adoption varies based on factors such as age, education, and business experience. Therefore, digital marketing training and support from the government and trader associations are needed to accelerate the adoption of this technology. This study is expected to provide recommendations for the development of more effective digital marketing strategies for traditional market traders in South Sulawesi, in order to increase competitiveness and strengthen the local economy.